2022
DOI: 10.3389/fphar.2022.912618
|View full text |Cite
|
Sign up to set email alerts
|

Why We Need to Take a Closer Look at Genetic Contributions to CYP3A Activity

Abstract: Cytochrome P450 3A (CYP3A) subfamily enzymes are involved in the metabolism of 40% of drugs in clinical use. Twin studies have indicated that 66% of the variability in CYP3A4 activity is hereditary. Yet, the complexity of the CYP3A locus and the lack of distinct drug metabolizer phenotypes has limited the identification and clinical application of CYP3A genetic variants compared to other Cytochrome P450 enzymes. In recent years evidence has emerged indicating that a substantial part of the missing heritability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 116 publications
0
10
0
Order By: Relevance
“…CYP3A plays a critical role in the metabolism of drugs and other exogenous and endogenous substances, and its function is modified by genetic factors (Zhai et al, 2022). CYP3A4*1G affects drug metabolisms by altering CYP3A4 expression and enzyme activity in vivo and in human liver tissues (Miura et al, 2011;He et al, 2014;Yuan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…CYP3A plays a critical role in the metabolism of drugs and other exogenous and endogenous substances, and its function is modified by genetic factors (Zhai et al, 2022). CYP3A4*1G affects drug metabolisms by altering CYP3A4 expression and enzyme activity in vivo and in human liver tissues (Miura et al, 2011;He et al, 2014;Yuan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 It has been suggested that transcriptional regulators, such as HNF3γ and PXR, contribute to the observed variability in CYP3A4 activity. 2,10,11 More recently, associations between variants in the testis-specific Y-encoded-like proteins (TSPYLs) family and CYP3A activity have been reported. This family consists of TSPYL1 to TSPYL6, all of which are involved in many bio-functions, including chromatin remodeling 12 and transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, although it is estimated that 60%–80% of the variability of the enzyme activity is heritable, single nucleotide variants (SNVs) in the CYP3A4 gene only explain ~10% of the observed interindividual variability in CYP3A4 activity 8,9 . It has been suggested that transcriptional regulators, such as HNF3γ and PXR , contribute to the observed variability in CYP3A4 activity 2,10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, PXR and CAR are primarily expressed in the liver and gastrointestinal tract (Nishimura et al, 2004;Petrick and Klaassen, 2007) and are key transcription factors that govern the expression of genes encoding drug metabolizing enzymes including cytochrome P450s (CYPs) (Forman et al, 1998;Lehmann et al, 1998;Goodwin et al, 1999;Sueyoshi et al, 1999), UDP-glycosyltransferases (Sugatani et al, 2001;Sugatani et al, 2004), glutathione-S-transferases (Knight et al, 2008), sulfotransferases (Yetti et al, 2018), and drug transporters such as multidrug resistance protein 1 (MDR1) (Geick et al, 2001;Synold et al, 2001;Burk et al, 2005). A regulated gene set of particular note is the CYP3A family due to its known activity on the majority of clinically applied drugs (Zhai et al, 2022). PXR and CAR binding to chemicals results in subsequent nuclear translocation, binding to target gene promoters, and enhanced transcription.…”
Section: Introductionmentioning
confidence: 99%